Answer Key: Top Questions For Practice Definite Integration
Answer Key: Top Questions For Practice Definite Integration
Answer Key
#MathBoleTohMathonGo
www.mathongo.com
Top
Questions for Practice Definite Integration
Answer Keys and Solutions JEE Main 2022 Crash Course
Q1 (3)
Let I = ∫
0
2 cot x
cot x+cosec x
dx
⇒ I = ∫
0
2 cos x
cos x+1
dx
π
cos x+1−1
⇒ I = ∫
0
2
cos x+1
dx
2 1
⇒ I = ∫ (1 − π
) dx
0 2
2 cos
2
2 1 2 x
⇒ I = ∫ (1 − sec ) dx
0 2 2
π
x 2
⇒ I = (x − tan )
2
0
π
⇒ I = ( − 1) − (0 − 0)
2
π 1
⇒ I = − 1 = (π − 2).
2 2
π
2 cot x 1
dx = m(π + n)
0 cot x+cosec x 2
⇒ mn = −1
Q2 (2)
2
I = ∫
0
xp (x)dx
′′
′ 2 ′
I = x[p (x)] − ∫ p (x)dx
0 0
′
= 2p (2) − (p(2) − p(0))
= 2(−1) − (3 − 3)
= −2
Q3 (1)
π
I = ∫x
4
e
−x
(cosec x + cot x cosec x)dx.
Put −x = t ⇒ dx = −dt
−π
= − ∫ −π
4 t
e (− cosec(t) + cot(t) ⋅ cosec(t))dt
6
−π
−π −π
t
= e cosec t∣ −π = −√2e
4
4 + 2e 6
#MathBoleTohMathonGo
www.mathongo.com
Top
Questions for Practice Definite Integration
Answer Keys and Solutions JEE Main 2022 Crash Course
−π −π
= 2e 6
− √2e 4
⇒ a + b = 2 − √2
Q4 (4)
e
Pn = ∫
1
(log x) dx
n
Integrating by parts taking (log x) as first function and 1 as second function, we get
n
n e n−1 1
Pn = (log x) x| − ∫ x ⋅ n(log x) ⋅ dx
1 1 x
e e
⇒ Pn = e − n [ (log x)
n−1
⋅ x∣
∣
1
− ∫
1
x ⋅ (n − 1)(log x)
n−2
⋅
1
x
dx]
e n−2
= e − n [(e − 0) − (n − 1) ∫ (log x) dx]
1
= e − ne + n(n − 1)Pn−2
Q5 (2)
2 3 3
I = ∫
1
{x}dx + ∫
2
2
{x} dx + ∫
2
{x} dx
3
1 6+4+3
= ∫
0
(x + x
2
+ x ) dx =
3 1
2
+
1
3
+
1
4
=
12
=
13
12
I
⇒ 24 ( ) = 2.
13
Q6 (4)
We have,
200
−1
∫ [tan x] dx
0
tan 1 200
= ∫ [tan
−1
x] dx + ∫ [tan
−1
x] dx
0 tan 1
200
= 0 + ∫ 1dx
tan 1
200
= (x) = 200 − tan 1
tan 1
Q7 (3)
2 1 √5
2
∫ [x − x + 1] dx = 2 + +
0 2 2
#MathBoleTohMathonGo
www.mathongo.com
Top
Questions for Practice Definite Integration
Answer Keys and Solutions JEE Main 2022 Crash Course
Q8 (4)
π
I = ∫
0
4
[sin x + cos x](cos x − sin x)dx
√2 √2
⇒ I = ∫ [t]dt = ∫ 1dt = √2 − 1
1 1
Q9 (3)
π
sin x
(i)
2 2
Let I = ∫ dx … . .
0 sin x cos x
2 +2
π π
sin( −x)
2 2
2
⇒ I = ∫
2 π π
sin( −x) cos( −x)
2 2 +2 2
π
cosx
2 2
⇒ I = ∫ … … (ii)
0 cos x sin x
2 +2
π sin z cos x
2I = ∫
0
2
2
sin z
+2
cos x
dx
2 +2
π π
⇒ 2I = ∫
0
2
1 ⋅ dx = [x]
2
⇒ 2I =
π
π
⇒ I =
4
Q10 (10)
a
∫
0
f (x)dx = 10
a f (x)
I = ∫
−a 1+g(x)
dx … … … . . (1)
Using King
a f (−x)
I = ∫
−a 1+g(−x)
dx
a g(x)f (x)dx
⇒ I = ∫
−a 1+g(x)
a a
⇒ 2I = ∫
−a
f (x)dx = 2 ∫
0
f (x)dx
#MathBoleTohMathonGo
www.mathongo.com
Top
Questions for Practice Definite Integration
Answer Keys and Solutions JEE Main 2022 Crash Course
a
⇒ I = ∫
0
f (x)dx = 10
Q11 (2)
199π 1−cos 2x
Let, I = ∫
−π
√(
2
)dx
199π
= ∫
−π
| sin x|dx
π
= (199 − (−1)) ∫
0
| sin x|dx
nT
(∵ | sin x| is periodic with period π and ∫ mT
f (x)dx = (n − m) ∫
0
T
f (x)dx if T is the period of the function f (x)) .
π
= 200 ∫
0
sin xdx
π
= 200| − cos x|
0
Q12 (3)
Given,
2 − x cos x
f (x) = , g(x) = loge x
2 + x cos x
2 − x cos x
⇒ g(f (x)) = loge ( )
2 + x cos x
2 − (−x) cos(−x)
⇒ g(f (−x)) = loge ( )
2 + (−x) cos(−x)
2 + x cos x
⇒ g(f (−x)) = loge ( )
2 − x cos x
2 − x cos x
⇒ g(f (−x)) = − log( )
2 + x cos x
a
a
2∫ f (x)dx, f (−x) = f (x)
0
By using the property of definite integration, ∫ f (x)dx = { , we can write
−a 0, f (−x) = −f (x)
π
Q13 (3)
#MathBoleTohMathonGo
www.mathongo.com
Top
Questions for Practice Definite Integration
Answer Keys and Solutions JEE Main 2022 Crash Course
Given,
3π
2
P = ∫ f (cos x) dx … (i)
0
π
2
Q = ∫ f (cos x) dx … (ii)
0
nT
∫
0
g(x)dx = n ∫
T
0
g(x)dx where, n ∈ I and T is the period of g(x)
π
P = 3∫
0
f (cos
2
x) dx = 3Q
∴ P − 3Q = 0
Q14 (3)
1/x log t
1
f ( ) = ∫ dt
x 1 1+t
−1
Put t = u
1
dt = 2
du
− log x −1
= ∫
x
1 1
(
u
2
) du
(1+ )
x
− log x
= ∫
x
1 u(1+u)
du
x log t log t
F(x) = f (x) + f (
1
x
) = ∫
1 1+t
+
t(1+t)
dt
2 x
log t (log t)
x ∣ ∣
= ∫
1 t
dt =
∣ 2 ∣
1
2
(log x)
=
2
1
∴ F (e) =
2
Q15 (1)
Given,
x
f (x) = sin x + ∫
0
′
f (t) (2 sin t − sin
2
t) dt
′
f (x) = cos x + f (x) (2 sin x − sin
′ 2
x)
′ 2
f (x) (1 − 2 sin x + sin x) = cos x
′ cos x
f (x) = 2
sin x−2 sin x+1
f (x) = ∫
cos x
(sin x−1)
2
dx
1 1
= − + c = + c
sin x−1 1−sin x
when x = 0
∴ f (0) = 1 + c = 0 ⇒ c = −1
#MathBoleTohMathonGo
www.mathongo.com
Top
Questions for Practice Definite Integration
Answer Keys and Solutions JEE Main 2022 Crash Course
∴ f (x) =
1
1−sin x
− 1
1−1+sin x
=
1−sin x
sin x
=
1−sin x
Q16 (4)
Applying L'Hospital's Rule, for numerator we have to apply Newton Leibnitz integral rule
2 4
2(x−1)×(x−1) cos(x−1) −0
limx→1 (
(x−1) cos(x−1)+sin(x−1)
)(
0
0
)
Divide (x − 1)
2 4
2(x − 1) cos(x − 1)
= lim
x→1 sin(x−1)
cos(x − 1) +
(x−1)
0
=
1 + 1
= 0
Q17 (3)
x
12
f (x ) 4x
4 3 6
− x f (x ) 2x = 2π cos(2πx)
2
Putting x = 1
⇒ 4f (1) − 2f (1) = 2π
⇒ 2f (1) = 2π ⇒ f (1) = π
Q18 (8)
2n 2 3 2
r
3r 3
2 x
lim ∑ e n3 = ∫ 3x e dx
n→∞ 3
n 0
r=1
3
2
x
= [e ]
0
8 8 0
= e − 1 = e − e
Hence, a + b = 8
Q19 (1)
limn→∞
π
6
∑
n
r=1
sec (
2
6n
rπ
) × (
1
n
)
1
=
π
6
∫
0
sec (
2 xπ
6
)dx
#MathBoleTohMathonGo
www.mathongo.com
Top
Questions for Practice Definite Integration
Answer Keys and Solutions JEE Main 2022 Crash Course
1
∣ tan( xx ) ∣
π 6 π 1
= ∣
∣
= tan − tan 0 =
6 ∣ π ∣ 6 √3
∣ 6
∣
0
Q20 (1)
1
yn = {(1 +
1
n
) (1 +
2
n
) … (1 +
n
n
)}
yn = ∏
n
r=1
(1 +
r
n
)
n
ln(yn ) =
1
n
∑
n
r=1
ln(1 +
r
n
)
n 1 r
⇒ limn→∞ ln(yn ) = limn→∞ ∑ ln(1 + )
r=1 n n
1
⇒ ln(L) = ∫
0
ln(1 + x)dx
4
⇒ ln(L) = ln( )
e
⇒ L =
4
[L] = 1
#MathBoleTohMathonGo
www.mathongo.com